Protein markers useful in authenticating eurycoma longifolia contained herbal aphrodisiac products - Vejayan, J.; Iman, V.; Foong, S.L.; Ibrahim, H. (Faculty of Science, University of Malaya, 2013)
Eurycoma longifolia has been widely recognized for its aphrodisiac benefits and many herbal products incorporated with its extract been sold worldwide. The products in various forms of capsules or spherical tablets were appropriately solubilized in water and their protein content were separated using two dimensional electrophoresis (IPG strip of pI 3-10; 15% homogenous gel) and stained in coomassie blue. In this study using a standardized extract known for its biological activity, CFPR-JV1, two distinctive protein markers were detected within 2DE gel. The markers were spots found approximately at molecular weight of 14kDa at the basic extremities. The markers were not detected in a selected herbal product devoid of Eurycoma longifolia extract. In screening markers on a total of 23 National Pharmaceutical Control Bureau (NPCN) approved and 6 NPCB un-approved products claimed to have included Eurycoma longifolia extracts gave results with 18 of the 29 (approximately 62%) products observed with the presence of at least marker A, while the rest did not show presence of any markers. This enabled authentication of the products tested related to its active constituent. It is expected that the protein markers in addition to the existing chemical marker, Eurycomanone, may serve to be useful in authenticating genuine, unadulterated or sufficiently enough amount of Eurycoma longifolia in herbal aphrodisiac products.